Post-Job Creation Amdal Reform: Integration of Transcendental Values and Local Wisdom in Sustainable Development - Ridwan Ridwan; Rizka Rizka; Didik Irawansah; Ainun Wulandari; Warda Said; Wirda Rohmah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to examine the implications of the AMDAL policy reform in the Job Creation Law on sustainable development, while also offering an integrative model that combines a transcendental approach (prophetic law) and local wisdom. Using a juridical-normative research method with a legislative approach, a conceptual approach, and an analytical approach, this study critically analyzes changes in AMDAL regulations after the Job Creation Law and their impact on environmental protection. The results of the study reveal three main findings: first, the simplification of AMDAL procedures has the potential to reduce the effectiveness of environmental protection; second, there is a gap between the new policy and the principles of sustainable development; third, transcendental values derived from prophetic law and the local wisdom practices of indigenous communities can function as a corrective and complementary mechanism to the shortcomings of the new regulations. The study's conclusions indicate that the reformulation of AMDAL policy needs to consider the integration of transcendental values and local wisdom to create a more holistic environmental protection system. The proposed policy recommendations include: (1) strengthening local community participation in the AMDAL process; (2) internalizing prophetic law principles in implementing regulations; and (3) development of an environmental impact evaluation model based on local values. These findings provide an important contribution to the development of environmental policies that are more responsive to ecological and socio-cultural sustainability aspects.